ETHNOMATHEMATICS OF KAWUNG SOLO BATIK AS A LEARNING MEDIA FOR STREAM-BASED GEOMETRY TRANSFORMATION - TOHA, ANDI MUHAMMAD; SEPTI, ALEZA DWI; ASTUTI, WIWIN; BISRI, MOH. (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research is a literature study assessment that uses exploratory techniques with an ethnographic approach. The aim of this research is to explore Solo kawung batik as a learning medium for geometric transformations. The form of batik called